PERBEDAAN EFEKTIVITAS MENGUNYAH BUAH MENTIMUN (CUCUMIS SATIVUS L.) DENGAN BUAH NANAS MADU (ANANAS COMOSUS L. MERR) TERHADAP PLAK GIGI PADA SISWA KELAS VIII A DAN VIII B SMP NEGERI 13 BANJARBARU - nor, della; Rahmawati, Ida; Ulfah, Rasuna; Sabatul Habibah, Siti (JURNAL TERAPIS GIGI DAN MULUT, 2025)
Fresh foods rich in minerals, fiber, vitamins, and water such as fruits and vegetables can help clean teeth by increasing saliva production and chewing ability. There are many types of fruit that can be consumed to help maintain oral hygiene, including cucumber and pineapple. This study aims to determine the difference in the effectiveness of chewing cucumber fruit with honey pineapple fruit on dental plaque in students of class VIII A and VIII B SMP Negeri 13 Banjarbaru. This type of research is a quasi experimental with pretest posttest two group design. The number of samples was 45 respondents using total sampling technique. Data analysis using Paired and Independent Sample T-Test. The results showed that the plaque value before chewing cucumber was 2.74 and after chewing cucumber was 1.40 with a difference value of 1.34 while before chewing honey pineapple was 2.75 and after chewing honey pineapple was 0.90 with a difference value of 1.85. Paired test shows that the probability value (p=0.000 <0.05). Independent test shows that the probability value (p=0.004 <0.05) then H0 is rejected and Ha is accepted. The conclusion that honey pineapple fruit is more effective for reducing dental plaque means that there is a difference in the effectiveness of chewing cucumber fruit with honey pineapple fruit on dental plaque in students of class VIII A and VIII B SMP Negeri 13 Banjarbaru. It is recommended for students and teachers to be able to utilize fruits such as cucumber and honey pineapple as natural alternative ingredients to clean teeth by chewing.